Bridging the regulatory gap: a call for a regional, evidence-informed approach to e-cigarette control in Latin America - Izquierdo-Condoy, Juan S. (Frontiers in Public Health, 2025)
Electronic cigarettes, a subset of electronic nicotine delivery systems (ENDS), have rapidly gained global popularity, with adolescent and young adult uptake emerging as a key public health concern. Promoted as “healthier alternatives” to smoking and often marketed as cessation aids, these devices have not created the anticipated risk-reduction environment and instead threaten to erode hard-won gains in tobacco control. While international experience highlights the potential effectiveness of policies such as taxation, age restrictions, marketing bans, and smoke-free environment laws, results remain heterogeneous and context-dependent, with enforcement playing a critical role. In Latin America, tobacco use declined from 28% in 2000 to 16.3% in 2020 under the World Health Organization (WHO) Framework Convention on Tobacco Control (FCTC), yet electronic cigarette regulation has lagged, resulting in what can be described as an “unregulated epidemic.” Policy responses remain fragmented: some countries enforce comprehensive bans, others apply partial measures, and many still lack specific frameworks, leaving critical gaps in taxation, surveillance, and digital marketing oversight. This regulatory asymmetry facilitates youth-oriented market expansion and the re-normalization of nicotine consumption. Drawing on global lessons, this perspective argues that Latin America must avoid replicating the decades-long delay experienced with tobacco regulation. Instead, the region requires harmonized, evidence-informed, and context-sensitive frameworks that integrate ENDS-specific measures—such as flavor restrictions, comprehensive advertising bans, nicotine caps, and strict control of online sales—supported by robust enforcement and multisectoral coordination. Such an approach offers the best opportunity to contain this unregulated epidemic, safeguard public health, and protect future generations across the region.